Anti-Prion Systems Block Prion Transmission, Attenuate Prion Generation, Cure Most Prions as They Arise and Limit Prion-Induced Pathology in Saccharomyces cerevisiae - Reed B. Wickner; Herman K. Edskes; Moonil Son; Songsong Wu (Biology, 2022)
All variants of the yeast prions [PSI+] and [URE3] are detrimental to their hosts, as shown by the dramatic slowing of growth (or even lethality) of a majority, by the rare occurrence in wild isolates of even the mildest variants and by the absence of reproducible benefits of these prions. To deal with the prion problem, the host has evolved an array of anti-prion systems, acting in normal cells (without overproduction or deficiency of any component) to block prion transmission from other cells, to lower the rates of spontaneous prion generation, to cure most prions as they arise and to limit the damage caused by those variants that manage to elude these (necessarily) imperfect defenses. Here we review the properties of prion protein sequence polymorphisms Btn2, Cur1, Hsp104, Upf1,2,3, ribosome-associated chaperones, inositol polyphosphates, Sis1 and Lug1, which are responsible for these anti-prion effects. We recently showed that the combined action of ribosome-associated chaperones, nonsense-mediated decay factors and the Hsp104 disaggregase lower the frequency of [PSI+] appearance as much as 5000-fold. Moreover, while Btn2 and Cur1 are anti-prion factors against [URE3] and an unrelated artificial prion, they promote [PSI+] prion generation and propagation.